2013
DOI: 10.1074/jbc.m112.378984
|View full text |Cite
|
Sign up to set email alerts
|

The Import of the Transcription Factor STAT3 into Mitochondria Depends on GRIM-19, a Component of the Electron Transport Chain

Abstract: Background: Apart from its mitochondrial localization, mechanistic details of STAT3 import and assembly in mitochondria remain elusive. Results: Using an in vitro import assay, we show that STAT3 associates with the mitochondrial inner membrane in a GRIM-19-dependent manner. Conclusion: GRIM-19 chaperones the recruitment of STAT3 into mitochondrial inner membrane complexes. Significance: This study identifies a novel function of GRIM-19 and a mechanism for STAT3 import into mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
208
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(218 citation statements)
references
References 48 publications
8
208
2
Order By: Relevance
“…Studies have identified a Stat3-Grim-19 complex in the nucleus, cytoplasm and mitochondria (Bu et al, 2013;Li et al, 2012;Lufei et al, 2003;Zhang et al, 2003). Indeed it has recently been demonstrated that Grim-19 is required for Stat3 translocation to the mitochondria (Tammineni et al, 2013). We have demonstrated that in cells undergoing TNFa-induced necroptosis, Stat3 is phosphorylated on serine 727 by the necrosome, composed of RIPK-3, and in some instances, RIPK-1 (Shulga and Pastorino, 2012).…”
Section: R E T R a C T I O Nmentioning
confidence: 75%
“…Studies have identified a Stat3-Grim-19 complex in the nucleus, cytoplasm and mitochondria (Bu et al, 2013;Li et al, 2012;Lufei et al, 2003;Zhang et al, 2003). Indeed it has recently been demonstrated that Grim-19 is required for Stat3 translocation to the mitochondria (Tammineni et al, 2013). We have demonstrated that in cells undergoing TNFa-induced necroptosis, Stat3 is phosphorylated on serine 727 by the necrosome, composed of RIPK-3, and in some instances, RIPK-1 (Shulga and Pastorino, 2012).…”
Section: R E T R a C T I O Nmentioning
confidence: 75%
“…As Wegrzyn and colleagues 37 found, the immunoprecipitates of mitochondrial extracts yielded from mouse liver captured by a monoclonal antibody specifically targeted to the components of the ETC complex I contained STAT3 and NDUFA13. Using highly purified rat heart mitochondria in vitro, Tammineni et al 39 further discovered that STAT3 most likely resides in the inner mitochondrial membrane (IMM), facing toward the matrix. STAT3 import and translocation across the mitochondrial membrane requires membrane potential and, likely, energy.…”
Section: The Structure and Subcellular Localization Of Stat3mentioning
confidence: 99%
“…The C terminus of STAT3, especially Ser727, is required for the NDUFA13-dependent import and integration of STAT3 into complex I because mutating serine 727 to alanine reduces the import of STAT3 into mitochondria, even in the presence of NDUFA13. 39 …”
Section: The Structure and Subcellular Localization Of Stat3mentioning
confidence: 99%
“…It has already been shown that p53 can be imported into mitochondria by co-transport mechanisms via interaction with proteins such as mtHsp70, 19 Tid1, 68 mitochondrial helicase RECQL4, 60 or OKL38. 69 Furthermore, a very recent study described an import mechanism of the STAT3 nuclear protein into the mitochondrial matrix via an interaction with GRIM-19, a subunit of respiratory chain complex I, 70 supporting the fact that such proteins can also be involved in protein transport into mitochondria. However, the decrease of p53 in cells treated with siOSCP could depend on specific modifications of mitochondrial physiology due to OSCP knockdown.…”
Section: Discussionmentioning
confidence: 99%